Long-term high-intensity interval training reduces blood glucose in type 2 diabetes mellitus patients - Waskito Aji Suryo Putro; Muhammad Furqon Hidayatullah; Muchsin Doewes; Sapta Kunta Purnama; Slamet Riyadi; Fadilah Umar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to demonstrate the long-term effects of high-intensity interval training (HIIT) on reducing blood glucose levels in patients with type 2 diabetes mellitus. The research employs a preexperimental design with a one-group pretest‒posttest design. A total of 20 patients with type 2 diabetes mellitus, aged 40–60 years, participated in the study and received the HIIT intervention three times per week for eight weeks. Data collection involved measuring fasting blood glucose levels before and after the HIIT intervention via the ONE TOUCH™ BASIC™ Plus Meter. Data analysis was conducted via paired sample t tests with a significance level of 5%, and the effect size was evaluated via Cohen's d. Paired sample t test analysis between pre-HIIT and post-HIIT blood glucose levels (181.50±17.85 mg/dL to 99.50±8.26 mg/dL, p ≤ 0.001) revealed a significant reduction, with a large effect size (Cohen's d = 5.896). This study confirms that long-term high-intensity interval training is effective in lowering fasting blood glucose levels to normal ranges in patients with type 2 diabetes mellitus.